Cryogenic front-end amplifier design for large SiPM arrays in the DUNE FD1-HD photon detection system. (1st November 2022) - Brizzolari, C.; Carniti, P.; Cattadori, C.; Cristaldo, E.; de la Torre Rojo, A.; Delgado, M.; Falcone, A.; Francis, K.; Gallice, N.; Gotti, C.; Guarise, M.; Montagna, E.; et al.
Abstract: The photon detection system of the first far detector (FD1-HD) of the DUNE experiment will detect scintillation photons produced by particle interactions in a kiloton-scale liquid Argon time projection chamber. The photon detectors of choice are silicon photomultipliers (SiPM), 6×6 mm 2 each, arranged in groups of 48, which present a significantly low impedance to the front-end electronics. This paper details the design of a cryogenic amplifier with exceptionally low white voltage noise of 0.37 nV√( Hz ), based on a silicon-germanium input transistor and a BiCMOS fully differential operational amplifier. It yields excellent single photoelectron resolution even at low overvoltage values. The signal rise time is below 100 ns, and the dynamic range is about 2000 photoelectrons at the typical operating overvoltage. It draws 0.7 mA from a single 3.3 V supply, for a power consumption of 2.4 mW per channel. Simplified models were developed to predict the single photolectron signal shape and the signal to noise ratio, with a good match to measured performance.